Eighteenth Dynasty imperial borders at the Cool Waters of Horus and Seth - Rita Simon (Pražské Egyptologické Studie)
Some of the rulers of the Eighteenth Dynasty applied the designations of “Cool Waters of Horus and Seth” for marking their borders. These terms most certainly referred to the northern and southern celestial borders of the Egyptian Empire, and although they were surely geographically inspired, they cannot be tied to any specific geographical locations. The probable location of “the Cool Water of Horus” can solely be found on the Yale fragment of a late Egyptian world map positioned in its north western corner at the outer edge of the primal waters of the cosmos, beyond the depiction of the foreign countries of the region. Interestingly, “the Cool Water of Seth” was contrasted with the location of that of Horus in some of the royal inscriptions of the Eighteenth Dynasty. It must have been placed along the outer margin of the southern border of the Egyp tian cosmos. According to the royal ideology of the Eighteenth Dynasty, the pharaoh – who simultaneously embodied the composite power of Horus and Seth as he received his legitimacy to rule from both gods – was responsible for ensuring the eternal unity and prosperity of Lower and Upper Egypt, the mighty earthly river of which would also have been fed by these heavenly waters. Because of the will of the two gods, the Eighteenth Dynasty rulers could extend their power not only over Egypt but even farther to the surrounding foreign countries as far as “the Cool Waters of Horus and Seth” were imagined at the outer edges of the cosmos. There lay the ideologically “legitimate” northern and southern borders of the Egyptian Empire or at least for some of the most dominant Eighteenth Dynasty pharaohs, who were regarded with great appreciation by later rulers attempting to follow suit in their own royal ideology from time to time in a somewhat altered form.